2014
DOI: 10.1007/978-3-319-09596-7_3
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Very Massive Stars

Abstract: In this chapter I review theoretical models for the formation of very massive stars. After a brief overview of some relevant observations, I spend the bulk of the chapter describing two possible routes to the formation of very massive stars: formation via gas accretion, and formation via collisions between smaller stars. For direct accretion, I discuss the problems of how interstellar gas may be prevented from fragmenting so that it is available for incorporation into a single very massive star, and I discuss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 161 publications
(179 reference statements)
0
36
0
Order By: Relevance
“…The existence of a physical m max -M ecl relation is thus taken to be established (Weidner et al 2014). Although the theory has been successful in describing the stellar contents of whole galaxies (e.g., Weidner et al 2013b), it has been debated if the relation exists (see Section 2.1 in Weidner et al 2013a for details) or if star formation is a purely stochastic process (e.g., Krumholz 2015). This is a fundamental issue for understanding galaxy-wide IMFs and how massive stars form, and we here thus stress that the data do not support the hypothesis that star formation is stochastic (see Section 7 of Kroupa 2015).…”
Section: The Binary Fraction Among the Ejected O Star Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a physical m max -M ecl relation is thus taken to be established (Weidner et al 2014). Although the theory has been successful in describing the stellar contents of whole galaxies (e.g., Weidner et al 2013b), it has been debated if the relation exists (see Section 2.1 in Weidner et al 2013a for details) or if star formation is a purely stochastic process (e.g., Krumholz 2015). This is a fundamental issue for understanding galaxy-wide IMFs and how massive stars form, and we here thus stress that the data do not support the hypothesis that star formation is stochastic (see Section 7 of Kroupa 2015).…”
Section: The Binary Fraction Among the Ejected O Star Systemsmentioning
confidence: 99%
“…For example, Hsu et al (2012Hsu et al ( , 2013 presented that L1641, the low-density star-forming region (containing as many as »1600 stars) of the Orion A cloud, is deficient of massive (O and early B) stars compared to the canonical IMF with 3-4σ significance and that with a probability of only 3% the southern region of L1461 and the ONC can be drawn from the same population, supporting that the high-mass end of the IMF is dependent on environmental density. In Section 4.2 of Krumholz (2015) three references (Calzetti et al 2010;Fumagalli et al 2011;Andrews et al 2013) are cited as containing evidence against a physical m max -M ecl relation. Weidner et al (2014) critically discuss these works, showing Andrews et al (2013) data to be entirely consistent with the physical m max -M ecl relation.…”
Section: The Binary Fraction Among the Ejected O Star Systemsmentioning
confidence: 99%
“…This points to the idea that the spin rates of the low-∆RV, wide and low-q spectroscopic binaries have seldom been modified since the stars were formed and thus reflect the outcome of the formation process. While the formation process of massive stars is heavily debated (e.g., Zinnecker & Yorke 2007;Tan et al 2014;Krumholz 2015), most theories agree on the need for disk-mediated accretion. In its simplest form, the collapse of the initial natal cloud and the gas-accretion phase concentrate by far more angular momentum in the central region than can be stored in a single star.…”
Section: The Nature Of the Low-velocity Peak And The Formation Of Masmentioning
confidence: 99%
“…The details of this process are under investigation (see recent reviews by, e.g., Tan et al 2014;Krumholz 2015;Motte et al 2017) and an increasing number of studies have suggested that they form through dynamical processes initiated by cloud formation (e.g., Schneider et al 2010a;Csengeri et al 2011;Peretto et al 2013;Nguyen-Luong et al 2013).…”
Section: Introductionmentioning
confidence: 99%